The Effectiveness Of School Operational Assistance Program Implementation In Improving Teacher Performance And Education Quality In Elementary Schools - Triana Susanto; Suhartono Suhartono (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2022)
School Operational Assistance (BOS) is an Indonesian government program that aims to provide funding for operational costs for basic educations as a part of compulsory education programs. The research was conducted to analyze the effectiveness of the implementation of the BOS program in improving teaching performance and education quality. This study used a qualitative descriptive approach by using informants, including school principals, school treasurers, teachers, and school committees. Informants were selected by using purposive sampling technique and carried out to obtain data and produced an analysis of the field phenomena regarding the BOS program using the GOEM (Goal Oriented Evaluation Model) evaluation model. Indicator instruments include the preparation, structure, distribution, use, monitoring, reporting. The results showed that: (1) In general, the effectiveness of the implementation of the BOS program in the Kedu sub-district was appropriate in accordance with the BOS technical guidelines. (2) The effectiveness of the current use of the BOS fund program was less effective in improving teaching performance in pedagogic competence because BOS funds were not well targeted. In conclusion, innovative strategy is needed to improve learning programs as a the main targets.